Practice Patterns of Academic Urologists for Evaluating Microscopic Hematuria—How Well are We Following the Guidelines?. Issue 2 (March 2019) - Samson, Patrick; Waingankar, Nikhil; Shah, Paras; Han, Justin
Abstract: Introduction: Asymptomatic microscopic hematuria is a common clinical entity that may portend significant urinary tract disease. Guidelines vary in how asymptomatic microscopic hematuria should be evaluated, with the AUA (American Urological Association) guidelines arguably being the most comprehensive. We evaluated the practice patterns of academic urologists with respect to the 2012 AUA asymptomatic microscopic hematuria guidelines. Methods: Records of patients who underwent evaluation for asymptomatic microscopic hematuria between 2012 and 2015 were retrospectively examined. The use of imaging, cystoscopy and urine cytology was analyzed. Factors such as age, gender, smoking status, history of nonurological malignancy, history of pelvic irradiation, presence of irritative voiding symptoms, use of anticoagulation, number of red blood cells on microscopic urinalysis and evaluation by an oncology fellowship trained urologist were assessed. Multivariable logistic regression analysis was performed to explore the association between patient or physician factors and adherence to the AUA guidelines. Results: Among 1, 049 patients with asymptomatic microscopic hematuria 247 (23.5%) were evaluated in complete accordance with AUA guidelines. Rates of adherence to the guidelines regarding imaging, cytology and cystoscopy were 48.2%, 54.2% and 72.5%, respectively. Much of nonadherence was due to lack of cross-sectional imaging (46.4%) and excessive use of urine cytology (45.8%). Guideline adherence was independently associated with smoking history, irritative voiding symptoms, history of nonurological malignancy and evaluation by a nononcology trained urologist. Conclusions: Overall adherence of urologists to the AUA asymptomatic microscopic hematuria guidelines was suboptimal. Efforts in limiting the use of urine cytology to high risk patients may be the most effective way of improving adherence.